Political and legal analysis of the mechanisms of providing Ukraine with resources of strategic importance in the context of increasing the national defence potential - Tsyrfa Iuliia; Kopiika Valerii; Minhazutdinov Ihor; Doroshko Mykola; Medvedieva Maryna (2024)
This study addresses the critical issue of enhancing Ukraine’s defence capabilities through the efficient management of strategic resources amidst ongoing Russian aggression. The research aims to develop substantiated recommendations for optimizing the legal and political mechanisms that govern the provision of strategic resources to Ukraine. The study employs a formal legal method to analyze key national and international legal frameworks, including the Law of Ukraine “On the National Material Reserve” and the Code of Ukraine “On Subsoil,” focusing on their efficacy in wartime conditions. Also, political analysis, comparative analysis, legislative review and document analysis were used. The research highlights the gaps in existing legislation, particularly in adapting to the needs of martial law and the complexities of interagency coordination. The findings reveal that while Ukraine has established an extensive legal framework for managing strategic resources, significant issues persist in areas such as transparency, interagency cooperation, and bureaucratization. The study advocates for legislative amendments to better suit wartime needs, the implementation of a unified monitoring system, and enhanced international cooperation, particularly with bodies like the UN and World Bank. The conclusions emphasize the importance of Ukraine’s participation in international transparency initiatives and the need to align national legislation with EU standards. Overall, the thesis of this work is the development of substantiated recommendations for optimizing Ukraine’s strategic resource management in the context of war, while the research niche focuses on the analysis of political and legal mechanisms that influence the state’s defence capabilities.